The domestic water supply puzzle in Zimbabwean cities: challenges and opportunities for Mtapa residential suburb, Gweru, Zimbabwe - Matsa, Mark; Tapfuma, Tafadzwa (Center for Promoting Ideas, 2016)
Zimbabwe’s economic meltdown decade of 2000-2009 virtually paralyzed all socio-economic sectors including services delivery in urban areas. Economic sanctions imposed by the West, coupled with the climate change threat have only exacerbated the urban services delivery nightmare, especially the water delivery system. Notwithstanding, not all hope is lost. This study sought to assess the urban domestic water supply challenges and opportunities in Gweru’s Mtapa (or Mutapa) suburb using questionnaires, interviews and direct observations. Questionnaires were self-administered to 56 systematically selected residents of Mtapa Sections 5 and 6, while interviews were conducted with 3 purposively sampled key respondents who included Gweru Residents Association Organizing Secretary, Councillor for ward 6 which covers Mtapa suburb, and Chief Water Technician responsible for water supply. Results confirm that Mtapa suburb faces serious water supply challenges. Over 50% of the respondents confirmed that the unreliable water supply situation has affected their use of the toilet and they now live in fear of diarrhoeal diseases due to this unsanitary situation. Over 80% of the respondents have a negative perception in terms of water service delivery. Women have been largely affected by this situation in that they cannot fetch enough water for all domestic purposes mainly due to the distance to the alternative water sources (boreholes). There are, however, a number of feasible opportunities which can be pursued to improve this poor water supply situation in Mtapa and the city of Gweru in general. The study recommends that Gweru City Council avoids politicizing agreements with international organizations to help reduce the water problems because this will block these organizations from financially and technically helping in service delivery. The study also recommends that City Council resume pumping of water into reservoir tanks so that in cases of emergency or breakdown of pumps, water will be available for domestic use by residents. This can be achieved since there is now the involvement of international organizations for financial assistance.